(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2017)
Introduction: Treatment of multi drug resistant Mycobacterium tuberculosis (MDR-TB) with second line drugs is associated with adverse drug reactions and toxicity. Aim of this study were to determine side effects associated with drugs used in treatment of multi drug resistant tuberculosis and treatment related factors of MDR-TB patients. Methodology: A prospective study was carried out in National Tuberculosis Centre Bhaktapur Nepal. Questionnaires were used to collect data from patients. Results: Total 101 MDR TB patients were included among them majorities were male (52%) and mean age of the patients was 31.2 years. Majority of patients (87.1%) had previous history of tuberculosis treatment and 54.5% were in intensive phase of treatment. The side effect associated with drugs used in treatment of MDR-TB reported by patients were joint pain (21.2%), nausea (20.3%), hearing disturbances (11%), gastrointestinal disturbance (9.9%), depression (9.6%), itching (8.1%), hypothyroidism (6.4%), dizziness (6.4%), seizures (3.8%) and hepatitis (3.5%). Last month 25.74% patients missed one or more doses of drugs and 3.9% missed drug doses due to side effect of drugs. Majorities of the patients used vehicle to reach health centre (92.07%), time to reach the health center (59.4%) were less than 30 minutes but majorities of patients (57.4%) were not satisfied by the counseling of health care worker. Conclusion: The finding of this study shows that in MDR patients 12.8% were found new cases. Last month 3.9% patients were stopped the drugs due to side effects of drugs. Majority of patients (57.4%) were not satisfied by counseling of health care worker. Treatment of multi drug resistant tuberculosis with second line anti tubercular drugs is associated with side effects, health care worker counseling to MDR- TB patients with full attention is essential to encourage the patient’s moral and complete the treatment. Timely managing the side effects of medication is important in helping people to complete their treatment. SAARC J TUBER LUNG DIS HIV/AIDS, 2017; XIV(1), Page: 1-6